Alzheimer's Disease Screening Tools for Asian Americans: A Scoping Review. (October 2021) - Lim, Sahnah; Chong, Stella; Min, Deborah; Mohaimin, Sadia; Roberts, Timothy; Trinh-Shevrin, Chau; Kwon, Simona C.
With growing numbers of aging Asian Americans, Native Hawaiians, and Pacific Islanders (AANHPIs), the availability of culturally and linguistically appropriate screening tools for Alzheimer's disease and its related dementias (ADRD) is needed. The aim of this scoping review is to summarize the tools that have been adapted for and validated among the AANHPI population. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol for systematic reviews, six databases were searched for peer-reviewed articles describing ADRD among AANHPIs. Among 1, 477 articles screened for inclusion, 15 articles were included in the final analysis. Results showed a paucity of studies that psychometrically validate tools among this population. Furthermore, studies that culturally adapted and/or translated existing tools mostly targeted East Asian American populations. Our review provides a first step in mapping the extant literature on ADRD screening tools for this underresearched population and will serve as a guide for future research, policy, and intervention.